Nível de atividade física entre professores de Educação Física das escolas de educação básica de Pelotas - RS - Canabarro, Lucio Kerber (2010)
To estimate the level of physical activity is important for planning interventions, however there are few studies that investigate the teacher´s behavior in this aspect. Objective: the aim of this study was to verify, through a cross-sectional study, the level of physical activity of Primary school and high school physical education teachers working in the urban area of the city of Pelotas, southern Brazil. Method: a census study, using the IPAQ long to check the level of physical activity in the leisure of these professionals. Results: 188 teachers answered the questionnaire, 61.0% females, 54.8% completed post graduation studies and 55.9% were classified as active in leisure time. The level of physical activity during leisure time, in the adjusted analysis, presented inverse association with smoking (p=0.02) and direct with health s self-perception (p=0.001). Conclusion: The teachers presented a level of leisure time physical activity considered higher than those found in the population of Pelotas and have not shown the same risk factors for physical inactivity when compared with the population in general.